STUDI ANALISIS GAYA BELAJAR SISWA YANG MENGACU MODEL GRASHA-REICHMANN PADA MATA PELAJARAN KELOMPOK KEJURUAN KELAS X SMK KOMPETENSI KEAHLIAN TEKNIK GAMBAR BANGUNAN - suryaman suryaman; Tuti Iriani; Santoso Sri Handoyo (LPPM Universitas Negeri Jakarta, 2015)
This study was aimed to know the representation that refers to students' learning styles of Grasha Model-Reichmann in vocational subjects of 10th Grade of Vocational High School (VHS), Competency of Architecture Engineering. The study lasted from April to May 2015.This research is using a descriptive quantitative survey approach. The population in this study were all 10th students of 26 and 52 VHS of Jakarta with a total of 122 people. The sampling method is using the saturated sampling techniques with a total of 122 people. The techniques used for data collection are communication techniques and documentation. The instrument for students that are used in the form of a questionnaire from a total of 60 statements refers to Grasha-Reichmann Student Learning Style (GRSLS). The result is that there are 49 number of valid statement with very high reliability of (r11) = 0.96.Based on the research that has been done, the students' learning styles that is mainly used to the Subject of Building Construction is the collaborative learning style (78.93%), collaborative learning style (80.00%) for the Measure Soil Science Subjects, collaborative learning style (78.50%) for the Engineering Mechanics Subject, and participant learning styles (75.66%) for the Subject of engineering drawings.Results of interviews with teachers indicate that the Subject Building Construction, Measure Soil Science and Engineering Mechanics during the learning process using lecture while teaching style to the Subject engineering drawings using peer tutors. The difference between the student's learning style with teachers teaching style shows the results obtained by each student also had differences.